A Simplified Technique to Treat Bimaxillary Protrusion using Micro-osteoperforation: A Case Report - Anjali sudhakar kathade; Shruti rathi; Rizwan gilani; Ranjit kamble (Journal of Clinical and Diagnostic Research, 2023)
In Asian population, bimaxillary protrusion is a prevalent malocclusion characterised by protruding and proclined upper and lower incisors, as well as increased lip procumbence. A 25-year-old female patient presented with a chief complaint of forwardly placed teeth and bimaxillary protrusion and required fixed mechanotherapy with all four 1st premolar extractions. The patient also desired that the treatment be completed in a short period of time. Since sliding or loop mechanics alone take longer to close extraction spaces, authors chose Micro-osteoperforation (MOP), a minimally invasive procedure used to accelerate orthodontic tooth movement. MOP involves drilling or perforating distal to the canine for en-mass retraction, causing the alveolar bone to release inflammatory cells that accelerate tooth movement. This non invasive technique was used for the treatment. The average rate of tooth movement in each quadrant was 1.7 mm per month. Taking the procedure into account, the patient reported no side-effects during or after drilling, but mild discomfort was felt. The entire space closure took four months. At the end of space closure, a Class I molar and canine relationship was preserved with normal overbite and overjet, with very minimal anchorage loss on the molars. An extraoral improvement in profile from convex to straight was seen. The treatment was completed within 14 months. The novelty of MOP includes faster treatment times and less discomfort during orthodontic treatment. However, like any medical procedure, MOP does carry some risks, such as infection or damage to surrounding teeth or gums. It is important to discuss the risks and benefits of MOP with your orthodontist before deciding whether to undergo the procedure.